Risk factors for sudden infant death syndrome in a developing country Fatores de risco para síndrome da morte súbita do lactente em um país em desenvolvimento - Ana Paula Silveira Pinho; Denise Aerts; Magda Lahorgue Nunes (Universidade de São Paulo, 2008)
OBJECTIVE: To analyze whether previously identified risk factors for sudden death syndrome have a significant impact in a developing country. METHODS: Retrospective longitudinal case-control study carried out in Porto Alegre, Southern Brazil. Cases (N=39) were infants born between 1996 and 2000 who died suddenly and unexpectedly at home during sleep and were diagnosed with sudden death syndrome. Controls (N=117) were infants matched by age and sex who died in hospitals due to other conditions. Data were collected from postmortem examination records and questionnaires answers. A conditional logistic model was used to identify factors associated with the outcome. RESULTS: Mean age at death of cases was 3.2 months. The frequencies of infants regarding gestational age, breastfeeding and regular medical visits were similar in both groups. Sleeping position for most cases and controls was the lateral one. Supine sleeping position was found for few infants in both groups. Maternal variables, age below 20 years (OR=2, 95% CI: 1.1; 5.1) and smoking of more than 10 cigarettes per day during pregnancy (OR=3, 95% CI: 1.3; 6.4), significantly increased the risk for the syndrome. Socioeconomic characteristics were similar in both groups and did not affect risk. CONCLUSIONS: Infant-maternal and socioeconomic profiles of cases in a developing country closely resembled the profile described in the literature, and risk factors were similar as well. However, individual characteristics were identified as risks in the population studied, such as smoking during pregnancy and maternal age below 20 years. OBJETIVO: Analisar se fatores de risco previamente identificados para a síndrome da morte súbita do lactente têm impacto significativo em um país em desenvolvimento. MÉTODOS: Estudo retrospectivo, longitudinal, de caso-controle pareado realizado em Porto Alegre, RS. Os casos (N=39) foram lactentes nascidos entre 1996 e 2000 que morreram subitamente e inesperadamente em casa, ao dormir, com diagnóstico final da síndrome; o grupo controle (N=117) foi composto de lactentes pareados por idade e sexo que morreram em hospitais, por outra doença. Os dados foram coletados de registros médicos postmortem e respostas a questionários. Utilizou-se modelo de regressão logística para identificar os fatores associados ao desfecho. RESULTADOS: A idade média dos casos no momento da morte dos lactentes foi de 3,2 meses. As freqüências de idade gestacional, amamentação e visitas regulares a unidades básicas de saúde foram similares nos dois grupos. A posição de dormir mais comum nos casos e controles foi a lateral. A posição supina foi encontrada em alguns lactentes em ambos grupos. As variáveis maternas idade inferior a 20 anos (OR=2, IC 95%:1,1;5,1) e consumo de mais de 10 cigarros/dia durante a gravidez (OR=3, IC 95%: 1,3;6,4) aumentaram significativamente o risco para a síndrome. As características socioeconômicas foram similares entre os grupos e não afetaram o risco. CONCLUSÕES: Os perfis lactente-materno e os fatores de risco foram similares aos encontrados em outros países. Todavia, foram identificadas características individuais quanto aos riscos de fumar durante a gravidez e da idade materna inferior a 20 anos.